Restoration of Intracortical and Thalamocortical Circuits after Transplantation of Bone Marrow Mesenchymal Stem Cells into the Ischemic Brain of Mice. Issue 11 (November 2013) - Song, Mingke; Mohamad, Osama; Gu, Xiaohuan; Wei, Ling; Yu, Shan Ping
Transplantation of bone marrow mesenchymal stem cells (BMSCs) provides a promising regenerative medicine for stroke. Whether BMSC therapy could repair ischemia-damaged neuronal circuits and recover electrophysiological activity has largely been unknown. To address this issue, BMSCs were implanted into the ischemic barrel cortex of adult mice 1 and 7 days after focal barrel cortex stroke. Two days after the first transplantation (3 days after stroke), the infarct volume determined by TTC staining was significantly smaller in BMSC-treated compared to vehicle-treated stroke mice. The behavioral corner test showed better long-term recovery of sensorimotor function in BMSC-treated mice. Six weeks poststroke, thalamocortical slices were prepared and neuronal circuit activity in the peri-infarct region of the barrel cortex was determined by extracellular recordings of evoked field potentials. In BMSC-transplanted brain slices, the ischemia-disrupted intracortical activity from layer 4 to layer 2/3 was noticeably recovered, and the thalamocortical circuit connection was also partially restored. In contrast, much less and slower recovery was seen in control animals of barrel cortex stroke. Immunohistochemical staining disclosed that the density of neurons, axons, and blood vessels in the peri-infarct region was significantly higher in BMSC-treated mice, accompanied with enhanced local blood flow recovery. Western blotting showed that BMSC treatment increased the expression of stromal cell-derived factor-1 (SDF-1), vascular endothelial growth factor (VEGF), and brain-derived neurotrophic factor (BDNF) in the peri-infarct region. Moreover, the expression of the axonal growth associated protein-43 (GAP-43) was markedly increased, whereas the axonal growth inhibiting proteins ROCK II and NG2 were suppressed in the BMSC-treated brains. BMSC transplantation also promoted directional migration and survival of doublecortin (DCX)-positive neuroblasts in the peri-infarct region. The present investigation thus provides novel evidence that BMSC transplantation has the potential to repair the ischemia-damaged neural networks and restore lost neuronal connections. The recovered circuit activity likely contributes to the improved sensorimotor function after focal ischemic stroke and BMSC transplantation.